Low-Dose Tolvaptan for the Treatment of Dilutional Hyponatremia in Cirrhosis: A Case Report and Literature Review - Guo Shen; Hainv Gao (Case Reports in Hepatology)
Dilutional hyponatremia is common in decompensated cirrhosis and can be successfully treated by tolvaptan, a vasopressin V2-receptor antagonist. Data were lacking regarding the effects of tolvaptan on cirrhotic patients with a Child-Pugh score of >10 and a serum sodium concentration of <120 mmol/L. We report a case of forties man with a 20-year history of chronic hepatitis B presenting with yellow urine and skin. Laboratory tests demonstrated prolonged prothrombin time, markedly elevated total bilirubin, severe hyponatremia, and a Child-Pugh score of >10. The patient was diagnosed with dilutional hyponatremia and was treated with recommended dosage tolvaptan at first. The serum concentration of sodium recover but the patient felt obviously thirsty. As the dosage of tolvaptan was decreased accordingly from 15 mg to 5 mg, the patient still maintained the ideal concentration of serum sodium. This case emphasizes that cirrhotic patient with higher Child-Pugh scores and serum sodium concentration of <120 mmol/L can be treated with lower dose of tolvaptan.